Teachers, Human Rights and Human Rights Education: Knowledge, perspectives and practices of primary school teachers in Ireland - Pike, Susan (Centre for Human Rights and Citizenship, DCU, 2011)
Article 26 of the Universal Declaration of Human Rights (UDHR) states that education shall be directed towards “the strengthening of respect for human rights and fundamental freedoms” (United Nations, 1948, Art 26.2). This right to human rights education (HRE) is reiterated in all major human rights instruments which Ireland, along with most states in the world, has ratified. International programmes recognise the crucial role played by teachers in “bringing alive the spirit of human rights” in school practice (UNESCO, 2003, p.3) and request that states enable teachers to implement HRE in schools and classrooms (Committee on the Rights of the Child (CRC), 2006; OHCHR and UNESCO, 2006). This study provides the first national baseline data in relation to primary teachers’ understanding of human rights and HRE and contributes to the development of a research base on HRE in Ireland. The study aimed to ascertain the level of awareness of and attitudes towards human rights and HRE among primary school teachers in Ireland, to assess the extent to which HRE is implemented in primary schools, and to identify the challenges and opportunities for HRE in the primary system. The study was carried out by the Centre for Human Rights and Citizenship Education (CHRCE), St Patrick’s College, Dublin. The findings of the study help identify the needs of teachers and schools in relation to the delivery of HRE and also point to the level of compliance of the Irish state with regard to its commitment to implement HRE in primary schools. The principal research tool was a structured questionnaire specifically designed for the purpose of the study. The questionnaire consisted of both open and closed questions which were intended to produce quantitative and qualitative data. The questionnaire was rigorously piloted to ensure that the format, question structure and sequence were unambiguous, accessible, unbiased and appropriate to the aims of the study (Cohen, Manion and Morrison, 2000). Data collection took place in 2009. The questionnaire was distributed by post to 376 teachers in 188 primary schools (two teachers per school) throughout Ireland. 152 teachers from 110 schools returned the questionnaire. The sample was broadly representative of teachers in Irish primary schools in terms of gender, teaching experience and teaching role. While the study’s findings were positive in relation to respondents’ attitudes and openness towards human rights and HRE, the results echo international concerns regarding the level of knowledge of human rights and human rights instruments amongst teachers (Osler and Starkey, 2010; Imber, 2008; Casas, Saporiti, Gonzalez, Figuer, Rostan, Sadurni, Alsinet, Gusó, Grignoli, Mancini, Ferrucci and Rago, 2006; Fritzsche, 2006; Tibbitts, 2002). What emerged from the survey are many examples of practices occurring in primary schools and classrooms which respond to human rights concerns and incorporate rights respecting approaches. However, these activities tend not to be connected explicitly to human rights language and principles. Furthermore, despite much of the literature reflecting the potential for HRE to provide transformative learning experiences and critique social injustices (Tibbitts and Kirscshlaeger, 2010; Magendzo, 2005; Tibbitts, 2002, 2005), respondents’ conceptualisation of human rights tended to ignore hierarchical social structures, whilst their approach to HRE focused on improved social cohesion rather than empowerment.
Keywords: Identities in Transformation; Inclusive Society; Making Ireland